2003
DOI: 10.1007/s00500-003-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy orderings in flexible query answering systems

Abstract: This paper describes the benefits of using fuzzy orderings in flexible query answering systems. We provide a brief overview of those results from the theory of fuzzy orderings that are necessary to couple fuzzy orderings with flexible querying in a meaningful synergistic way. As one case study, we discuss a simple and pragmatic variant of a flexible query answering system -the so-called Vague query system (VQS). The integration of fuzzy orderings into that system is provided in full detail along with examples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Bodenhofer and Klawonn [6] propose a fuzzy extension of the gamma coefficient based on concepts of fuzzy orderings and -equivalence relations, where denotes a t-norm [4]. A fuzzy relation E : U × U → [0, 1] is called fuzzy equivalence with respect to a t-norm , for brevity -equivalence, if it is reflexive (E(u, u) = 1),…”
Section: Fuzzy Equivalence and Order Relationsmentioning
confidence: 99%
“…Bodenhofer and Klawonn [6] propose a fuzzy extension of the gamma coefficient based on concepts of fuzzy orderings and -equivalence relations, where denotes a t-norm [4]. A fuzzy relation E : U × U → [0, 1] is called fuzzy equivalence with respect to a t-norm , for brevity -equivalence, if it is reflexive (E(u, u) = 1),…”
Section: Fuzzy Equivalence and Order Relationsmentioning
confidence: 99%
“…For more information regarding to fuzzy orders constructed on the base of fuzzy equivalence relations see [5], [4]. In general L defined by (1) is not a fuzzy order relation.…”
Section: ] Is Called Fuzzy Order Relation With Respect To a T-norm T mentioning
confidence: 99%
“…Fuzzy order relation defined as above can be widely used in practical applications, see e.g. [5]. In our paper, studying the process of A-Taggregation, we focus on the preservation of Ttransitivity where initial fuzzy order relation are given by (2).…”
Section: ] Is Called Fuzzy Order Relation With Respect To a T-norm T mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experience with modern information retrieval systems has shown that users are not willing to learn special query languages and formulate non-trivial boolean queries. Thus, even something like a fuzzy SQL might still not be a full solution to the problem (see, for example, [2,3,4,5,6,7] and many others).…”
Section: Introductionmentioning
confidence: 99%